Sulfuric acid decomposition on the Pt/n-SiC catalyst for SI cycle to produce hydrogen - Noh, Seong-Cheol; Lee, Seoung Young; Shul, Yong Gun; Jung, Kwang-Deog (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The sulfuric acid decomposition should be performed in the wide temperature ranges from 550 degrees C to 950 degrees C to absorb the sensible heat of He in SI process. Therefore, the catalysts for the reaction should be stable even in the very corrosive reaction condition of 650 degrees C. Here, the Pt/n-SiC catalyst was prepared for the purpose and compared with the Pt/SiC catalyst. The both catalysts showed the high stability in the temperature ranges from 650 to 850 degrees C. The n-SiC with the surface area of 187.1 m(2)/g was prepared using nano-sized SiO2, which resulted in amorphous SiC phase. The SiC support with the surface area of 19.2 m(2)/g for the comparison showed the well crystalline structure. In spite of the large surface area differences between the n-SiC and SiC support, the Pt particle sizes of the Pt/n-SiC (average Pt size: 26.4 nm) catalyst were not so much different from those of the Pt/SiC (average Pt size: 26.1 nm) catalyst after the calcination at 1000 degrees C for 3 h. However, the catalytic activity of the Pt/n-SiC was much higher than that of the Pt/SiC. XRD analysis indicated that the Pt particles on the Pt/n-SiC was more stable than those of the Pt/SiC in the sulfuric acid decomposition and XPS analysis showed that the Pt valence state on the Pt/n-SiC was higher than that on the Pt/SiC. The surface analysis showed that the surface of the n-SiC particles was covered by SiO2 and Si4C4-xO4. These experimental results indicate that the Pt metal particles on n-SiC were stabilized on the oxidized Si surface. Therefore, it is suggested that the Pt particles stabilized on the oxidized Si surface can be a reason for the higher activity of the Pt/n-SiC catalyst as compared with the Pt/SiC catalyst. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: THERMOCHEMICAL HYDROGEN; SO3 DECOMPOSITION; IODINE CYCLE; OXIDATION; OXIDE; STABILITY; GRANULES; OXYGEN; STATES; XPS